2015
DOI: 10.5551/jat.29090
|View full text |Cite
|
Sign up to set email alerts
|

Different Impacts of Cardiovascular Risk Factors on Arterial Stiffness versus Arterial Wall Thickness in Japanese Patients with Type 2 Diabetes Mellitus

Abstract: Aim:We statistically investigated whether the impact of cardiovascular risk factors on arterial stiffness would be different from that on arterial wall thickness. Methods: We analyzed 1648 Japanese type 2 diabetic patients. Arterial stiffness was evaluated by pulse wave verbosity (PWV) and wall thickness was assessed with carotid intima-media thickness (IMT) by ultrasonography. We developed a common regression model to PWV and IMT by extending the linear mixed model and statistically detected the difference in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 58 publications
2
9
0
Order By: Relevance
“…It is clearly established that the CVR strongly influences the increase in arterial stiffness. 25,26 In present study, there was a positive correlation between PWVft and CVR; this was confirmed in the literature for other populations than SCT.…”
supporting
confidence: 79%
“…It is clearly established that the CVR strongly influences the increase in arterial stiffness. 25,26 In present study, there was a positive correlation between PWVft and CVR; this was confirmed in the literature for other populations than SCT.…”
supporting
confidence: 79%
“…Moreover, BMI was a strong determinant of aortic PWV, but not carotid IMT, in obese T2D patients in the U.S 35) . On the other hand, dyslipidemia 21, 33) and hyperglycemia 34, 35) , but not obesity-related indices, were preferentially associated with carotid IMT in subjects with T2D. In addition, we found that only obesity-related indices were significantly different between the men with higher stiffness but lower IMT and the men with lower stiffness but higher IMT.…”
Section: Discussionmentioning
confidence: 52%
“…Differential impact of cardiovascular risk factors on arterial stiffness and IMT were also observed in Japanese patients with T2D 21, 33, 34) . Consistent with our results, several studies reported that the association with obesity-related measures was different between arterial stiffness and IMT 21, 35) .…”
Section: Discussionmentioning
confidence: 73%
“…Recent studies have even reported that arterial calcification could be found in the earlier course of atherosclerosis as a circumferential lesion 21) . Actually, arterial stiffness may share a lot of cardiovascular risk factors with atherosclerosis, such as age, sex, hemoglobin A1c, systolic blood pressure, and serum cholesterol, as shown in a study in patients with type 2 diabetes mellitus exploring the risk factors for baPWV and intima-media thickness 22) . Furthermore, the locations of stiffening have some differences between the selected markers.…”
Section: Discussionmentioning
confidence: 99%